Revisiting the methodology of Myrdal in Asian Drama 50 years on - Frances Stewart (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
This paper reviews the main methodological innovations in Asian Drama. It considers whether Myrdal's perspectives have been adopted by development analysts, and where fresh thinking is needed, particularly in the light of changes occurring in the half-century since he wrote Asian Drama. The paper concludes that many of his ideas have been accepted, especially among heterodox economists, some themselves putting forward similar arguments. Mainstream economics has, in general, been the least responsive, and renewed emphasis is needed - especially with regard to the effects of positionality on concepts, theories, and policies; and on the inappropriateness of some advanced country economic concepts. In Asian Drama, Myrdal fails to consider that some concepts are inappropriate for the analysis of advanced economies, too. The critical need to take into account environmental considerations in the 21st century provides an additional reason for seeking alternative frameworks for everywhere, whether North or South.
Keywords: O10; O20; O50; O57; P50; N35; 330; development; Myrdal; values; institutions; attitudes